Exploring inclusive education in times of COVID-19: An international comparison of German, Austrian and Portuguese teachers - Letzel-Alt, Verena; Pozas, Marcela; Schwab, Susanne; Schneider, Christoph; Lindner, Katharina-Theresa; Dias, Paulo; Cadime, Irene (Frontiers in Education, 2022)
With the start of the Coronavirus (COVID-19) pandemic, the global education system has a faced immense challenges and disruptions resulting in and the necessity for an immediate redesign of teaching and learning in the school context. Face-to-face classroom instruction had to be replaced by ‘emergency remote teaching’, requiring teacher to adapt their daily routines to a new and unprecedented educational reality. Researchers and policymakers worldwide have agreed that, despite the fact that efforts were made to immediately adapt to emergency remote teaching, disadvantaged and vulnerable students may be especially at risk in emergency remote teaching. Given the differences in schooling organization across countries during the COVID-19 pandemic it can be expected that teachers performed inclusive instructional practices significantly different. Against the unpredictable situation, cross-country research has been urgently required to provide data that could inform education policy. Thus, this study explored teachers’ perceptions of supporting at risk students during the first COVID-19 school closures, as well as examining teachers’ inclusive teaching practices in three countries: Germany, Austria and Portugal. ANOVA results revealed important country differences. In general, it appears that teachers in Germany and Austria reported to have implemented less practices to address vulnerable and at-risk students compared to Portuguese teachers. Implications of the results, as well as further lines of research are outlined.